Analisis Determinan Bantuan Teknis Bank Indonesia Pada Profitabilitas UMKM di Provinsi Jambi (2013-2015) - Maratun Sholihah; AA Miftah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
The purpose of this study is to determine the effect of Bank Indonesia technical assistance on the development of MSMEs in Jambi Province in 2013-2015. This thesis uses a descriptive quantitative approach with data collection methods through observation, interviews, questionnaires and documentation. The results show that Bank Indonesia technical assistance for the development of MSMEs in Jambi Province has a significant effect of 0.637. If technical assistance increases by 1%, MSME development will increase by 0.637. The partial test results on the regression model obtained results of 0.000 <0.05 (significant level of research results). In the variable t count> from t table, namely 5,430> 2,021, it can be concluded that accept Ha and reject Ho means that partially the variable technical assistance affects the development of MSMEs. The R square obtained is 0.391 which means that 39.1% of the diversity of Bank Indonesia technical assistance affect the diversity of levels of MSME development in Jambi Province. While the remaining 60.9% is influenced by other variations not mentioned in the variables. The obstacles in providing technical assistance include the easy come and easy go pattern of MSMEs, MSMEs that have not dared to expand their businesses, not many business actors have not mastered technology. Meanwhile, the results achieved by Bank Indonesia are: the existence of trust from the banking sector and the increase in business partners from MSMEs, an increase in business volume, the formation of LKMAs that are able to make MSMEs independent in their business development, increasing knowledge of the importance of business records, increasing product quality, human resources UMKM players, and the existence of market development and expansion.